Ranpirnase Eradicates Human Papillomavirus in Cultured Cells and Heals Anogenital Warts in a Phase I Study. Issue 3 (April 2017) - Squiquera, Luis; Taxman, Debra J; Brendle, Sarah A; Torres, Roberto; Sulley, Jamie; Hodge, Thomas; Christensen, Neil; Sidransky, David
Background: Human papillomaviruses (HPV), the causative agents of anogenital warts, are the most prevalent sexually transmitted infectious agents, and wart treatment poses a persistent challenge. We assessed the safety and efficacy of treating HPV with ranpirnase, an endoribonuclease from the northern leopard frog that has been used extensively in Phase III oncology trials. Methods: As initial verification of ranpirnase antiviral activity, we assessed its ability to eliminate papilloma-viruses in cultured cells. To further assess its feasibility for treating anogenital warts in humans, we performed a Phase I study. Forty-two male volunteers with genital/ perianal warts were treated topically with three different formulations of 1 mg/ml ranpirnase. Patients were monitored for 8 weeks or until healing. Four patients with HIV were treated in accordance with the compassionate programme but were not evaluated. Results: In cultured cells, ranpirnase showed specific activity against HPV-11 with low toxicity (selectivity index >88). The broad applicability of ranpirnase for treating papillomaviruses was verified using the cottontail rabbit papillomavirus. In the clinical study, eight participants were lost-to-follow-up or discontinued due to protocol violation or non-compliance. Among 30 evaluable participants, topical ranpirnase was moderately well-tolerated, with discontinuation by 5 (16.7%) due to adverse reactions. Clinical healing was achieved by 25 participants (83.3%) and 50% improvement by the 5 discontinued participants (16.7%). The median time to clinical healing was 30 days. Conclusions: This study provides the first in vitro and clinical evidence of the antiviral efficacy of ranpirnase against HPV and supports assessment of ranpirnase in expanded clinical studies.